Enhancing Drought Tolerance in Salicornia ramosissima Through Biofertilization with Marine Plant Growth-Promoting Bacteria (PGPB) - Ricardo Cruz de Carvalho; João Albuquerque Carreiras; Ana Rita Matos; Isabel Caçador; Bernardo Duarte (Plants)
The duration, frequency, and intensity of drought events in the Mediterranean region pose increasing threats to conventional crop production. Consequently, eco-friendly and sustainable development approaches should aim to address future food production goals. Halophytes, such as Salicornia ramosissima J. Woods, represent promising cash crops for cultivation in conjunction with novel biofertilization strategies involving plant growth-promoting bacteria (PGPB). In the present study, the physiological fitness of S. ramosissima under various drought conditions, with and without marine PGPB inoculation, was evaluated to enhance the resilience of this cash crop halophyte under water-limited conditions. Our results indicate that PGPB inoculation significantly decreased water loss under extreme drought, with non-inoculated plants showing a water content (WC) of 59%, while in inoculated plants, the decrease in WC was lower at 77%. Furthermore, PGPB inoculation significantly enhanced the photochemistry of the plant, which maintained higher active oxygen-evolving complexes and a greater ability for complete closure of reaction centers under severe and extreme drought, thus demonstrating an improved capacity for light energy utilization in photosynthesis even under water-limited conditions. Furthermore, bioaugmented plants generally exhibited improved osmoregulation through increased yet appropriate accumulation of proline, a major osmolyte, and higher relative water content in the stem compared to the corresponding non-inoculated plants. Drought stress similarly modified the fatty acid profile in both plant groups, resulting in increased membrane stability due to reduced fluidity. However, PGPB-inoculated plants demonstrated a higher capacity for mitigation of oxidative stress, primarily through enhanced activities of superoxide dismutase, which is crucial for the scavenging of harmful reactive oxygen species (ROS). This, along with improvements in energy use and dissipation, as evidenced by photochemistry, reveals a multi-dimensional mechanism for drought tolerance in bioaugmented plants. Metabolic changes, particularly in PGPB-inoculated plants, clearly demonstrate the potential of these bacteria to be utilized in the enhancement of drought tolerance in S. ramosissima. Moreover, these data elucidate the complex metabolic aspects regarding photochemistry, osmoregulation, and oxidative stress that should be considered when phenotyping plants for drought tolerance, given the increasing water scarcity worldwide scenario.